Information and communication technology, inequality change and regional development in Indonesia - Chusnul Faizah; Kyohei Yamada; Devanto Shasta Pratomo (Publisher of Widyagama University of Malang (UWG Press), 2021)
Although the advancement of technology provides numerous opportunities to boost economic growth and development, equal distribution may not be guaranteed. Thus, this study seeks further elaboration as to whether ICT development has a role to play in the inequality in Indonesia. Using municipal level data from 2018, the study provides both linear and non-linear models to be estimated using OLS and 2SLS. Major findings include: (i) the availability of basic ICT infrastructure is strongly linked to the reduction of inequality; (ii) the actual ICT use is positively associated with inequality, albeit at a diminishing rate, revealing a non-linear relationship similar to Kuznets' curve; (iii) the ICT skill variable comprising the education level has direct correlation with ICT use instead of inequality, with an additional score on ICT skill being associated with an increase in ICT use; (iv) the relationship between ICT use and inequality differed depending on the level of economic development, with lower-income regions experiencing the inverted U-shaped relationship as in the original Kuznets curve and higher-income regions experiencing the U-shaped curve.JEL Classification: D63; I24; O10